The prevalence of anxiety and depression among MBBS students in the medical colleges in Thrissur district, Kerala during the shutdown of colleges due to the COVID-19 pandemic - Paul, Steve; Vincent, Jose (International Journal Of Community Medicine And Public Health, 2022)
Background: The medical students of India, who are already facing psychological challenges due to their existing study system will be much more significantly affected, including their academics and social interactions, because of the lockdown due to the COVID-19 pandemic. The aim of this study was to find the prevalence and determinants of anxiety and depression among MBBS students due to this. Methods: This was a cross sectional study and the setting were two medical colleges in Thrissur district, Kerala namely, Government Medical College and Amala Institute of Medical Sciences. The study subjects were the students undergoing MBBS course in these two medical colleges and the data was collected between July and December, 2020. The sample size was calculated as 200. Hospital anxiety and depression scale (HADS) questionnaire and attitude towards mental illness scale (AMI) questionnaire was used to obtain data along with relevant sociodemographic details. Stratified random sampling was used. Results: 26.2% and 13.1% of the participants had abnormal scores for anxiety and depression respectively. Out of all the participants that underwent isolation, 71.4% and 61.9% of them had abnormal scores for anxiety and depression respectively. Out of all the participants whose residential area had been a containment zone, 68% had normal score for depression. A minority of participants (8%, 3.3%) had unfavourable responses regarding their attitude towards mental illnesses. Conclusions: Our study established a significant prevalence of anxiety and depression among the participants and these results may be generalised to all Indian medical students. This study also showed that their attitude towards mental illness were not appropriate.